Perceived enablers and barriers of community engagement for vaccination in India: Using socioecological analysis. - Tapati Dutta (Public Library of Science (PLoS), 2021)
Background There is high level policy consensus in India that community engagement (CE) improves vaccination uptake and reduces burden of vaccine preventable diseases. However, to date, vaccination studies in the country have not explicitly focused on CE as an outcome in and of itself. Therefore, this study sought to examine the barriers and enablers of community engagement for vaccination in India. Methods Employing qualitative methods, twenty-five semi-structured elite interviews among vaccine decisionmakers' were triangulated with twenty-four national-level vaccine policy documents and researcher field notes (December 2017 to February 2018). Data collected for this study included perceptions and examples of enablers of and barriers to CE for vaccination uptake. Concepts, such as the absence of formal procedures or data collection approaches related to CE, were confirmed during document review, and a final convening to review study results was conducted with study respondents in December 2018 and January 2019 to affirm the general set of findings from this study. The Social Ecological Model (SEM) was used to organize and interpret the study findings. Results Although decisionmakers and policy documents generally supported CE, there were more CE barriers than facilitators in the context of vaccination, which were identified at all social-ecological levels. Interviews with vaccine decisionmakers in India revealed complex systemic and structural factors which affect CE for vaccination and are present across each of the SEM levels, from individual to policy. Policy-level enablers included decisionmakers' political will for CE and policy documents and interviews highlighted social mobilization, whereas barriers were lack of a CE strategy document and a broad understanding of CE by decisionmakers. At the community level, dissemination of Social-behavioral Change Communication (SBCC) materials from the national-level to the states was considered a CE facilitator, while class, and caste-based power relations in the community, lack of family-centric CE strategies, and paternalistic attitude of decisionmakers toward communities (the latter reported by some NGO heads) were considered CE barriers. At the organizational level, partnerships with local organizations were considered CE enablers, while lack of institutionalized support to formalize and incentivize these partnerships highlighted by several decisionmakers, were barriers. At the interpersonal level, SBCC training for healthcare workers, sensitive messaging to communities with low vaccine confidence, and social media messaging were considered CE facilitators. The lack of strategies to manage vaccine related rumors or replicate successful CE interventions during the during the introduction and rollout of new vaccines were perceived as CE barriers by several decisionmakers. Conclusion Data obtained for this study highlighted national-level perceptions of the complexities and challenges of CE across the entire SEM, from individual to systemic levels. Future studies should attempt to associate these enablers and barriers with actual CE outcomes, such as participation or community support in vaccine policy-making, CE implementation for specific vaccines and situations (such as disease outbreaks), or frequency of sub-population-based incidents of community resistance and community facilitation to vaccination uptake. There would likely be value in developing a population-based operational definition of CE, with a step-by-step manual on 'how to do CE.' The data from this study also indicate the importance of including CE indicators in national datasets and developing a compendium documenting CE best-practices. Doing so would allow more rigorous analysis of the evidence-base for CE for vaccination in India and other countries with similar immunization programs.